PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP IPA MATERI PERUBAHAN WUJUD BENDA - Nurbayanti, Fitri; Ruqoyyah, Siti; Savira Wardani, Duhita (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The aim of this research is to find out and examine the application of the Discovery Learning model to increase understanding of science concepts in the material on changes in the shape of objects, the difficulties of students and teachers in applying the Discovery Learning model to increase understanding of science concepts in the material on changes in the shape of objects. This research uses a mix method with the Sequential Explanatory Design. The instruments used in this research were tests, questionnaires and interview guides. The subjects in this research were 35 class V students at SDN Karyamulya. Apart from that, the difficulties faced by teachers are difficulty in providing motivation to students, limited teaching aids, difficulty managing time and difficulty conditioning students. Despite this, learning went well and optimally. Based on this, it can be concluded that the Discovery Learning learning model is effective in improving the ability to understand science concepts in grade V elementary school.